PENGEMBANGAN LEMBAGA PAUD MELALUI IMPLEMENTASI MANAJAMEN BERBASIS SEKOLAH - NURHASANAH R Nurhasanah R; FAJRI DWIYAMA (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract. The existence of early childhood education institutions in Indonesia has received special attention from the government as the initial foundation to build reliable human resources. But in its journey, the institution was confronted with quite a number of serious problems such as: First, the level of teacher education where only 23.06 percent had a bachelor degree, while according to the National Education Standards, PAUD teachers should have both formal and non-formal minimum S.1 PAUD, Psychology, or Education. Second, the problem of the quality of PAUD institution programs. Third, there is still one third of children aged 3-6 years who have not received PAUD services. Fourth, family involvement that is not in line with PAUD institutions. Fifth, PAUD learning which is supposed to be 80 percent building attitudes, is currently focusing on learning to read and write in an academic nuance. Sixth, problems with education investment.Seventh, nutrition problems and eighth, namely the status of non-formal PAUD teachers who have not been considered as teachers. Seeing so many problems in the management of PAUD institutions, a management approach is needed to deal with these problems. Recommended alternative problem solving is school-based management. This paper only expresses in outline to attract the interest of managers of early childhood education institutions to learn more about the implementation of school-based management.